A dosimetric study on radiation-induced hypothyroidism following intensity-modulated radiotherapy in patients with nasopharyngeal carcinoma - Xu, Yumei (Oncol Lett, 2018)
The objective of the present study was to investigate the association between thyroid gland-dosimetric parameters and hypothyroidism induced by intensity-modulated radiotherapy in patients with nasopharyngeal carcinoma (NPC). A total of 52 patients with NPC treated in the Department of Radiation Oncology of The Affiliated Hospital of Xuzhou Medical University, from May 2008 to December 2016 were retrospectively enrolled in the present study and divided into two groups based on thyroid function: The euthyroid and hypothyroid groups. The association between hypothyroidism and clinical or dosimetric parameters were analyzed. Females had a significantly increased probability of suffering from radiation-induced hypothyroidism (RIHT), compared with males (P=0.010). The occurrence of RIHT was significantly negatively associated with thyroid volume prior to radiotherapy (P=0.048). Furthermore, the mean dose (Dmean) and V50 in the hypothyroidism group were significantly increased, compared with the euthyroidism group (P=0.017 and P=0.023, respectively). During the treatment optimization period, dose constraints associated with the thyroid gland demonstrated a significantly protective effect on thyroid function compared with the unconstrained group (P=0.034). According to the receiver operating characteristic curves, the threshold value was 5,160 cGy for Dmean and 54.5% for V50. The 3-year cumulative incidence of RIHT was 67.8% when the Dmean value was >5,160 cGy and 44.6% when the Dmean was <5,160 cGy (log rank test, P=0.036). Furthermore, the 3-year cumulative incidence was 66.1% when the V50 was >54.5%, and 29.9% when the V50 was <54.5% (log rank test, P=0.025). In conclusion, RIHT is associated with radiation dose, particularly with Dmean and V50 of the thyroid gland. Dose constraints associated with the thyroid gland significantly reduced the incidence of hypothyroidism compared with the unconstrained group.